Blueprints for better reading: An inquiry into the nature of the reading process - Wagner, Rudolph P. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The reading process was critically examined in view of continually incoming research studies that may contribute towards the enhancement of improved reading instructions. The point of departure was seen in making inferences from reading pathology to normal reading functions. The salient dimensions of the reading process were discussed by stating eight basic postulates. A method for teaching normal children to read based on linguistic and psycho-pedagogical principles was suggested in a nine-phase sequence of teaching methodology. The suggested approach would allow to take normal children through a thorough reading procedure, while at the same time allowing to pick the slow readers and dyslexics. The poor readers could be singled out early and given additional and specific training, similar to the branching technique in programmed instructions.